A dielectric film for dry DC capacitor and its preparation process

Modified silica is prepared by polymer sol and silica sol composite process and supercritical drying, and combined with reinforcing materials and reaction aids, the problem of uneven dispersion of inorganic non-metallic materials in polypropylene is solved, and the anti-aging performance and service life of the dielectric film is significantly improved.

CN119775621APending Publication Date: 2025-04-08ZHEJIANG NANYANG HUACHENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing inorganic non-metallic materials are difficult to disperse evenly in polypropylene, resulting in unstable composite properties, insufficient anti-aging properties, and short service life.

Method used

Modified silica is prepared by supercritical drying by polymer sol and silica sol composite process, and combined with a specific proportion of reinforcement materials and reaction aids, dielectric films with excellent mechanical properties and dielectric properties are prepared through melt kneading, mechanical stretching and multi-layer structure design.

Benefits of technology

The dispersion and stability of silica in polypropylene is significantly improved, the anti-aging performance and service life of the film are improved, and it has excellent dielectric strength and breakdown strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a dielectric film for dry-type DC capacitors and a preparation process thereof, and relates to the technical field of capacitor materials. The preparation process comprises: S100, preparing polymer sol, preparing silica sol, mixing the polymer sol with the silica sol and performing supercritical drying to obtain modified silica; S200, mixing modified polypropylene, modified silica, reinforcing material and reaction aid, and obtaining a polypropylene base film through melt mixing, casting and mechanical stretching; S300, vacuum evaporation treatment of the polypropylene base film, including sequentially performing base film pretreatment, first evaporation, first oxidation treatment, second evaporation and second oxidation treatment. The present invention adopts a special polymer sol and silica sol composite process to prepare modified silica, solves the technical problem that inorganic non-metallic materials are difficult to disperse uniformly in polypropylene, significantly improves the dispersibility and stability of silica in polypropylene materials, and improves the anti-aging performance and service life of polypropylene films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of capacitor materials, and in particular to the technical field of dielectric films for capacitors. Background Art

[0002] Dielectric film is a thin film material that is deposited with metal on a polymer base film such as polyester or polypropylene. The metal coating can be aluminum, zinc, zinc-aluminum alloy or other metals or alloys. Dielectric film has the characteristics of high square resistance. Under the same current, it will produce a higher voltage. Therefore, dielectric film has a wide range of application prospects in the field of dry DC capacitors.

[0003] Among the many types of base films, polypropylene film has the advantages of small specific gravity, stable chemical properties, low cost, mature technology, etc., and it can maintain a small dielectric thickness and good dielectric strength under the working voltage of high-voltage capacitors. Therefore, polypropylene film has become a base film material with great application prospects in the field of capacitors.

[0004] The disadvantage of polypropylene film is that its mechanical properties and mechanical strength are not ideal. The main way to improve the above properties of polypropylene film in the prior art is to add inorganic non-metallic materials such as silicon oxide, aluminum oxide, and zirconium oxide to polypropylene. However, the disadvantage of the prior art is that it is difficult for inorganic non-metallic materials to be uniformly and stably dispersed in polypropylene, resulting in the anti-aging performance of polypropylene film being not ideal and the service life also needs to be improved. Summary of the invention

[0005] The problem solved by the present invention is that existing inorganic non-metallic materials (such as silicon oxide, aluminum oxide, zirconium oxide, etc.) are difficult to disperse uniformly in a polypropylene matrix; due to the uneven dispersion, the performance of the composite material is unstable; the anti-aging performance of the film is not ideal; and the service life of the final product is short. In order to solve at least one of the above problems, the present invention provides a dielectric film for a dry DC capacitor and a preparation process thereof, the preparation process comprising the following steps:

[0006] S100, preparing a polymer sol and a silica sol, mixing the polymer sol and the silica sol and performing supercritical drying to obtain modified silica;

[0007] S200, mixing modified polypropylene, modified silicon dioxide, reinforcing material and reaction aid, and performing melt mixing, sheet casting and mechanical stretching to obtain a polypropylene base film;

[0008] S300, performing vacuum evaporation treatment on the polypropylene base film, including sequentially performing base film pretreatment, first evaporation treatment, first oxidation treatment, second evaporation treatment and second oxidation treatment.

[0009] In step S100, the specific process of preparing the polymer sol is as follows:

[0010] Add N-methyl-2-pyrrolidone, p-xylene and dimethylacetamide into a vacuum reactor, set the vacuum degree to ≤20Pa, and stir evenly at 30°C; add 1,2,4-trimethylbenzene anhydride and 4,4'-methylenebis(phenyl isocyanate), raise the temperature to 50°C and keep the temperature constant for 60 minutes; add diphenylmethane diisocyanate and phenol, stir evenly and keep the temperature constant for 60 minutes to obtain a polymer sol.

[0011] In step S100, the specific process of preparing silica sol is as follows:

[0012] Ethyl orthosilicate, ethanol and deionized water were mixed evenly, hydrochloric acid solution was added dropwise to adjust the pH value to 5, and the mixture was stirred at a constant temperature of 40°C for 10 minutes; sodium hydroxide aqueous solution was added dropwise to a pH value of 10, and the mixture was stirred at a constant temperature of 40°C for 60 minutes, and allowed to stand for 120 minutes to obtain silica sol.

[0013] In step S100, supercritical drying is performed under the following conditions:

[0014] With carbon dioxide as the medium, the temperature is 31°C to 33°C, and the pressure is 7.3MPa to 7.5MPa.

[0015] In step S200, in the preparation of the polypropylene base film:

[0016] The weight average molecular weight Mw of the modified polypropylene is 400,000, and the melt flow rate is 10 g / 10 min;

[0017] The reinforcement material includes polyetherimide chopped fibers and nano zirconium boride in a weight ratio of 1:5;

[0018] The reaction aid comprises γ-aminopropyltriethoxysilane and polyvinyl alcohol in a weight ratio of 1:8.

[0019] In step S300, the base film pretreatment includes:

[0020] The method comprises the following steps: performing corona discharge treatment twice, wherein the primary corona discharge treatment energy is 20-25 J / cm2 and the secondary corona discharge treatment energy is 50-52 J / cm2; applying 2-3‰ ammonium chloride solution between the two corona discharge treatments and drying at 85-90°C.

[0021] In step S300, the process parameters of the first evaporation are: the cooling spindle temperature is 0-1°C; the zinc crucible heating temperature is 780-790°C.

[0022] In step S300, the process parameters of the first oxidation treatment are:

[0023] A mixed gas of ozone and nitrogen with a volume fraction of 5-6‰ is introduced into a constant temperature oven at 120-125°C.

[0024] In step S300, the process parameters of the second evaporation are:

[0025] The cooling spindle temperature is -3~-1℃;

[0026] The heating temperature of the aluminum crucible is 1590~1600℃;

[0027] Control the thickness of the aluminum coating to half of the galvanized coating.

[0028] In step S300, the second oxidation treatment uses hydrogen peroxide with a mass fraction of 65-70% at 50-55°C to perform surface oxidation treatment.

[0029] The dielectric film for dry DC capacitors and the preparation process thereof provided by the present invention have the following beneficial effects:

[0030] The present invention adopts a special polymer sol and silica sol composite process, and the modified silica prepared by the sol-gel method has excellent mechanical properties and mechanical properties. The process can effectively reduce the surface energy of silica, significantly improve the dispersibility and stability of silica in polypropylene materials, and enable it to form a uniform and stable dispersion system in the polypropylene matrix, thereby improving the anti-aging performance and service life of the polypropylene film.

[0031] The present invention adopts a supercritical drying process, which is carried out under a temperature condition of 31° C. to 33° C. and a pressure condition of 7.3 MPa to 7.5 MPa, which can effectively prevent the gel network structure from collapsing, maintain the porous structure of the modified silica, increase its specific surface area, and enhance the interface bonding force with the polypropylene matrix.

[0032] The present invention further optimizes the interface structure of the composite material and improves the comprehensive mechanical properties of the film by adding a specific proportion of reinforcing materials (polyetherimide chopped fibers and nano zirconium boride) and reaction aids (γ-aminopropyltriethoxysilane and polyvinyl alcohol).

[0033] The present invention adopts a base film pretreatment process of twice corona discharge treatment combined with ammonium chloride solution coating, which significantly improves the bonding force between the metal layer and the base film and improves the electrical performance and stability of the film.

[0034] The present invention innovatively adopts a multilayer structure design of "zinc layer-oxide layer-aluminum layer-oxide layer". By precisely controlling the process parameters of two evaporation and oxidation treatments, a good interface structure is formed between the metal layer and the oxide layer, effectively improving the dielectric properties of the film.

[0035] The dielectric film prepared by the invention has excellent dielectric strength and breakdown strength, the breakdown field strength thereof can reach above 450V / μm, and the dielectric loss tanδ is ≤0.02%.

[0036] The preparation process of the invention is simple to operate, the process parameters are controllable, it is suitable for large-scale production, and the cost is low, so it has good industrial application prospects.

[0037] The accelerated aging test shows that the dielectric film prepared by the present invention has an attenuation amplitude of electrical and mechanical properties of no more than 5% under the condition of 125°C / 1000h, indicating that the product has excellent aging resistance and service life. DETAILED DESCRIPTION

[0038] The purpose of the present invention is to provide a dielectric film for dry DC capacitors and a preparation process thereof. Modified silica is prepared by a special polymer sol and silica sol composite process, and a supercritical drying process and a specific proportion of reinforcing materials and reaction aids are used to solve the technical problem of the difficulty in uniformly dispersing inorganic non-metallic materials in polypropylene in the prior art. At the same time, the dielectric properties, mechanical strength and anti-aging properties of the dielectric film are significantly improved by innovatively adopting a multilayer structure design of "zinc layer-oxide layer-aluminum layer-oxide layer", so that it has good application prospects in the field of dry DC capacitors.

[0039] To achieve the above-mentioned purpose, the method adopted by the present invention is S100, preparing a polymer sol and a silica sol, mixing the polymer sol with the silica sol and performing supercritical drying to obtain modified silica; S200, mixing modified polypropylene, modified silica, reinforcing materials and reaction aids, and obtaining a polypropylene base film through melt mixing, sheet casting and mechanical stretching; S300, vacuum evaporation treatment of the polypropylene base film, including sequentially performing base film pretreatment, first evaporation, first oxidation treatment, second evaporation and second oxidation treatment.

[0040] In the above technical solution, S100 specifically includes:

[0041] S101, add 400 parts by weight of N-methyl-2-pyrrolidone, 80 parts by weight of p-xylene and 40 parts by weight of dimethylacetamide into a vacuum reactor, set the vacuum degree to ≤20Pa, and stir evenly at 30°C; add 120 parts by weight of 1,2,4-trimethylbenzene anhydride and 60 parts by weight of 4,4'-methylenebis(phenyl isocyanate), raise the temperature to 50°C and keep the temperature constant for 60 minutes, finally add 100 parts by weight of diphenylmethane diisocyanate and 120 parts by weight of phenol, stir evenly and keep the temperature constant for 60 minutes to obtain a polymer sol;

[0042] S102, 30 parts by weight of ethyl orthosilicate, 100 parts by weight of ethanol, and 50 parts by weight of deionized water are mixed evenly, 6 wt % hydrochloric acid solution is added dropwise to adjust the pH value to 5, and the mixture is stirred at a constant temperature of 40° C. for 10 min to obtain a silica solution;

[0043] A 10 wt % sodium hydroxide aqueous solution was added dropwise as a catalyst to the silica precursor solution until the pH value reached 10, and the solution was stirred at a constant temperature of 40° C. for 60 min and allowed to stand for 120 min to obtain a silica sol;

[0044] S103, 20-30 parts by weight of the polymer sol and 60-80 parts by weight of the silica sol are uniformly mixed, and the mixture is immersed in anhydrous ethanol for aging for 24 hours, and the anhydrous ethanol is replaced every 2 hours to obtain a modified silica gel;

[0045] Using carbon dioxide as a medium, at a temperature of 31° C. to 33° C. and a pressure of 7.3 MPa to 7.5 MPa, the modified silica gel is supercritically dried to obtain modified silica.

[0046] In the above technical solution, S200 specifically includes:

[0047] S201, 90-100 parts by weight of modified polypropylene (weight average molecular weight Mw is 400,000, melt flow rate is 10g / 10min), 10-20 parts by weight of modified silica, 1-5 parts by weight of reinforcing material (polyetherimide chopped fibers [length 0.8mm, diameter 20μm] and nano zirconium boride [particle size 20nm], weight ratio is 1:5), 1-5 parts by weight of reaction aid (γ-aminopropyltriethoxysilane and polyvinyl alcohol, weight ratio is 1:8) are mixed uniformly to obtain a raw material mixture;

[0048] Wherein, the preparation method of the modified polypropylene is:

[0049] The polypropylene particles with a particle size of 0.6 mm were immersed in triallyl phosphate solution at 30°C for 2 hours, irradiated with electron beam at a dose of 20 kGy, heated to 60°C for 2 hours, washed and dried to obtain;

[0050] S202, adding the raw material mixture into a screw extruder, and performing melt mixing and extrusion at 220° C. to obtain a sheet-like fluid;

[0051] S203, casting the sheet-like fluid through a chilled roller at a temperature of 90° C. and a high-pressure air knife at a temperature of 90° C. to obtain a membrane;

[0052] S204, using a mechanical stretching machine to stretch the film longitudinally and transversely at 140° C., with a stretching ratio of 3:1;

[0053] The film was heat-set at 130° C. for 30 min and then cooled and solidified to obtain a polypropylene-based film.

[0054] In the above technical solution, S300 specifically includes:

[0055] S301, perform corona discharge treatment twice on the working surface of the polypropylene base film:

[0056] First level corona discharge treatment: 20-25 J / cm2, treatment voltage 5000V-15000V;

[0057] The product of the net voltage and net current treated is the energy unit, and the treated area of ​​the bottom layer of the plastic film is the area unit;

[0058] Apply 2-3‰ ammonium chloride solution and strictly control drying at 85-90℃;

[0059] Secondary corona discharge treatment: 50~52J / cm2;

[0060] S302, first evaporation:

[0061] Vacuum evaporation of zinc layer in the first vacuum coating machine:

[0062] Cooling spindle temperature: 0~1℃;

[0063] Zinc crucible heating temperature: 780~790℃;

[0064] Obtaining a zinc coating;

[0065] S303, first oxidation treatment:

[0066] Introduce oxidation treatment gas into a constant temperature oven at 120-125°C:

[0067] Gas composition: ozone (volume fraction 5-6‰) mixed with nitrogen;

[0068] By controlling the temperature and ozone concentration, a fluffy zinc oxide layer is formed on the surface of the galvanized layer;

[0069] S304, second evaporation:

[0070] Vacuum deposition of aluminum layer in the second vacuum coating machine:

[0071] Cooling spindle temperature: -3~-1℃, using low temperature rapid cooling;

[0072] Aluminum crucible heating temperature: 1590~1600℃;

[0073] Control the thickness of the aluminum coating to be half of the zinc coating;

[0074] S305, second oxidation treatment:

[0075] At a temperature of 50-55°C, the surface of the aluminum coating is oxidized using 65-70% hydrogen peroxide.

[0076] A dense aluminum oxide film is formed to obtain the final dielectric film.

[0077] [Example 1]

[0078] S1, add 400 parts by weight of N-methyl-2-pyrrolidone, 80 parts by weight of p-xylene and 40 parts by weight of dimethylacetamide into a vacuum reactor, set the vacuum degree to ≤20Pa, and stir evenly at 30°C; add 120 parts by weight of 1,2,4-trimethylbenzene anhydride and 60 parts by weight of 4,4'-methylenebis(phenyl isocyanate), raise the temperature to 50°C and keep the temperature constant for 60 minutes, finally add 100 parts by weight of diphenylmethane diisocyanate and 120 parts by weight of phenol, stir evenly and keep the temperature constant for 60 minutes to obtain a polymer sol;

[0079] S2, 30 parts by weight of ethyl orthosilicate, 100 parts by weight of ethanol, and 50 parts by weight of deionized water were mixed evenly, 6 wt% hydrochloric acid solution was added dropwise to adjust the pH value to 5, and the mixture was stirred at a constant temperature of 40° C. for 10 min to obtain a silica solution;

[0080] A 10 wt % sodium hydroxide aqueous solution was added dropwise as a catalyst to the silica precursor solution until the pH value reached 10, and the solution was stirred at a constant temperature of 40° C. for 60 min and allowed to stand for 120 min to obtain a silica sol;

[0081] S3, 20 parts by weight of the polymer sol and 80 parts by weight of the silica sol were mixed evenly, and the mixture was immersed in anhydrous ethanol for aging for 24 hours, and the anhydrous ethanol was replaced every 2 hours to obtain a modified silica gel;

[0082] Using carbon dioxide as a medium, the modified silica gel is supercritically dried under the conditions of a temperature of 32° C. and a pressure of 7.4 MPa to obtain modified silica.

[0083] S4, 90 parts by weight of modified polypropylene (weight average molecular weight Mw is 400,000, melt flow rate is 10g / 10min), 15 parts by weight of modified silica, 3 parts by weight of reinforcing material (polyetherimide chopped fibers [length 0.8mm, diameter 20μm] and nano zirconium boride [particle size 20nm], weight ratio is 1:5), 3 parts by weight of reaction aid (γ-aminopropyltriethoxysilane and polyvinyl alcohol, weight ratio is 1:8) are mixed uniformly to obtain a raw material mixture;

[0084] Wherein, the preparation method of the modified polypropylene is:

[0085] The polypropylene particles with a particle size of 0.6 mm were immersed in triallyl phosphate solution at 30°C for 2 hours, irradiated with electron beam at a dose of 20 kGy, heated to 60°C for 2 hours, washed and dried to obtain;

[0086] S5, adding the raw material mixture into a screw extruder, and performing melt mixing and extrusion at 220° C. to obtain a sheet-like fluid;

[0087] S6, passing the sheet fluid through a chilled roller at a temperature of 90° C. and a high-pressure air knife at a temperature of 90° C. to form a sheet, thereby obtaining a membrane;

[0088] S7, using a mechanical stretching machine to stretch the film longitudinally and transversely at 140° C., with a stretching ratio of 3:1;

[0089] The film was heat-set at 130° C. for 30 min and then cooled and solidified to obtain a polypropylene-based film.

[0090] In the above technical solution, S300 specifically includes:

[0091] S8. Perform corona discharge treatment twice on the working surface of the polypropylene base film:

[0092] First level corona discharge treatment: 22J / cm2, treatment voltage 10000V;

[0093] The product of the net voltage and net current treated is the energy unit, and the treated area of ​​the bottom layer of the plastic film is the area unit;

[0094] Apply 3‰ ammonium chloride solution and strictly control drying at 90℃;

[0095] Secondary corona discharge treatment: 52J / cm2;

[0096] S9, first evaporation:

[0097] Vacuum evaporation of zinc layer in the first vacuum coating machine:

[0098] Cooling spindle temperature: 1°C;

[0099] Zinc crucible heating temperature: 785℃;

[0100] Obtaining a zinc coating;

[0101] S10, first oxidation treatment:

[0102] Into the 125℃ constant temperature oven, introduce oxidation treatment gas:

[0103] Gas composition: ozone (volume fraction 5-6‰) mixed with nitrogen;

[0104] By controlling the temperature and ozone concentration, a fluffy zinc oxide layer is formed on the surface of the galvanized layer;

[0105] S11, second evaporation:

[0106] Vacuum deposition of aluminum layer in the second vacuum coating machine:

[0107] Cooling spindle temperature: -1℃, using low temperature rapid cooling;

[0108] Aluminum crucible heating temperature: 1600℃;

[0109] Control the thickness of the aluminum coating to be half of the zinc coating;

[0110] S12, second oxidation treatment:

[0111] At 55℃, the surface of the aluminum layer was oxidized using 70% hydrogen peroxide.

[0112] A dense aluminum oxide film is formed to obtain the final dielectric film.

[0113] [Example 2]

[0114] S1, add 400 parts by weight of N-methyl-2-pyrrolidone, 80 parts by weight of p-xylene and 40 parts by weight of dimethylacetamide into a vacuum reactor, set the vacuum degree to ≤20Pa, and stir evenly at 30°C; add 120 parts by weight of 1,2,4-trimethylbenzene anhydride and 60 parts by weight of 4,4'-methylenebis(phenyl isocyanate), raise the temperature to 50°C and keep the temperature constant for 60 minutes, finally add 100 parts by weight of diphenylmethane diisocyanate and 120 parts by weight of phenol, stir evenly and keep the temperature constant for 60 minutes to obtain a polymer sol;

[0115] S2, 30 parts by weight of ethyl orthosilicate, 100 parts by weight of ethanol, and 50 parts by weight of deionized water were mixed evenly, 6 wt% hydrochloric acid solution was added dropwise to adjust the pH value to 5, and the mixture was stirred at a constant temperature of 40° C. for 10 min to obtain a silica solution;

[0116] A 10 wt % sodium hydroxide aqueous solution was added dropwise as a catalyst to the silica precursor solution until the pH value reached 10, and the solution was stirred at a constant temperature of 40° C. for 60 min and allowed to stand for 120 min to obtain a silica sol;

[0117] S3, 25 parts by weight of the polymer sol and 75 parts by weight of the silica sol were mixed evenly, and the mixture was immersed in anhydrous ethanol for aging for 24 hours, and the anhydrous ethanol was replaced every 2 hours to obtain a modified silica gel;

[0118] Using carbon dioxide as a medium, the modified silica gel is supercritically dried under the conditions of a temperature of 31° C. and a pressure of 7.3 MPa to obtain modified silica.

[0119] S4, 90 parts by weight of modified polypropylene (weight average molecular weight Mw is 400,000, melt flow rate is 10g / 10min), 15 parts by weight of modified silica, 3 parts by weight of reinforcing material (polyetherimide chopped fibers [length 0.8mm, diameter 20μm] and nano zirconium boride [particle size 20nm], weight ratio is 1:5), 3 parts by weight of reaction aid (γ-aminopropyltriethoxysilane and polyvinyl alcohol, weight ratio is 1:8) are mixed uniformly to obtain a raw material mixture;

[0120] Wherein, the preparation method of the modified polypropylene is:

[0121] The polypropylene particles with a particle size of 0.6 mm were immersed in triallyl phosphate solution at 30°C for 2 hours, irradiated with electron beam at a dose of 20 kGy, heated to 60°C for 2 hours, washed and dried to obtain;

[0122] S5, adding the raw material mixture into a screw extruder, and performing melt mixing and extrusion at 220° C. to obtain a sheet-like fluid;

[0123] S6, passing the sheet fluid through a chilled roller at a temperature of 90° C. and a high-pressure air knife at a temperature of 90° C. to form a sheet, thereby obtaining a membrane;

[0124] S7, using a mechanical stretching machine to stretch the film longitudinally and transversely at 140° C., with a stretching ratio of 3:1;

[0125] The film was heat-set at 130° C. for 30 min and then cooled and solidified to obtain a polypropylene-based film.

[0126] In the above technical solution, S300 specifically includes:

[0127] S8. Perform corona discharge treatment twice on the working surface of the polypropylene base film:

[0128] First level corona discharge treatment: 22J / cm2, treatment voltage 10000V;

[0129] The product of the net voltage and net current treated is the energy unit, and the treated area of ​​the bottom layer of the plastic film is the area unit;

[0130] Apply 3‰ ammonium chloride solution and strictly control drying at 90℃;

[0131] Secondary corona discharge treatment: 52J / cm2;

[0132] S9, first evaporation:

[0133] Vacuum evaporation of zinc layer in the first vacuum coating machine:

[0134] Cooling spindle temperature: 1°C;

[0135] Zinc crucible heating temperature: 785℃;

[0136] Obtaining a zinc coating;

[0137] S10, first oxidation treatment:

[0138] Into the 125℃ constant temperature oven, introduce oxidation treatment gas:

[0139] Gas composition: ozone (volume fraction 5-6‰) mixed with nitrogen;

[0140] By controlling the temperature and ozone concentration, a fluffy zinc oxide layer is formed on the surface of the galvanized layer;

[0141] S11, second evaporation:

[0142] Vacuum deposition of aluminum layer in the second vacuum coating machine:

[0143] Cooling spindle temperature: -1℃, using low temperature rapid cooling;

[0144] Aluminum crucible heating temperature: 1600℃;

[0145] Control the thickness of the aluminum coating to be half of the zinc coating;

[0146] S12, second oxidation treatment:

[0147] At 55℃, the surface of the aluminum layer was oxidized using 70% hydrogen peroxide.

[0148] A dense aluminum oxide film is formed to obtain the final dielectric film.

[0149] [Comparative Example 1]

[0150] The polymer sol was not used to modify the silica, and ordinary silica powder was directly mixed with polypropylene. The remaining steps were the same as those in Example 1.

[0151] [Comparative Example 2]

[0152] No two corona discharge treatments and no oxidation treatments were performed, only a single-layer metal coating was performed, and the remaining steps were the same as in Example 1.

[0153] Performance Testing

[0154] The performance test results of the samples obtained in Examples 1 and 2, and Comparative Examples 1 and 2 are listed in Table 1.

[0155] Table 1

[0156] Performance Indicators Example 1 Example 2 Comparative Example 1 Comparative Example 2 Breakdown field strength test (V / μm) 465 458 380 365 Dielectric loss tanδ test (%) 0.015 0.018 0.035 0.042 Square resistance test (Ω / sq) 2.5 2.8 4.5 5.2 Accelerated aging test (%) 3.2 3.8 8.5 12.3

[0157] From Table 1, we can see that:

[0158] The breakdown field strength of Examples 1 and 2 is significantly higher than that of the comparative example, indicating that the uniform dispersion of modified silicon dioxide and the double-layer metallization structure can effectively improve the voltage resistance performance of the film; the comparative example 1 has uneven dispersion of unmodified silicon dioxide, resulting in local electric field concentration and reduced breakdown field strength; the comparative example 2 lacks oxide layer protection, the metal layer structure is unstable, and the breakdown field strength is the lowest.

[0159] The dielectric loss of Examples 1 and 2 is significantly lower than that of the comparative example, indicating that the modification process significantly improves the dielectric properties of the material; the high dielectric loss of comparative example 1 is due to the polarization loss caused by silica agglomeration; the interface polarization loss of comparative example 2 is relatively large due to the single-layer metal structure.

[0160] The square resistance values ​​of Examples 1 and 2 are significantly lower than that of the comparative example, indicating that the double-layer metallization structure improves the conductivity; the high square resistance values ​​of the comparative examples 1 and 2 affect the electrical properties and use effects of the film.

[0161] Examples 1 and 2 show excellent aging resistance, and the performance decay rate is significantly lower than that of the comparative example; the high decay rate of comparative example 1 is due to the local stress concentration caused by silica agglomeration; comparative example 2 lacks an oxidation protection layer, and the metal layer is easily oxidized and degraded, resulting in the highest decay rate.

[0162] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A dielectric film for a dry DC capacitor and a preparation process thereof, characterized in that: The preparation process comprises: S100, preparing a polymer sol and a silica sol, mixing the polymer sol and the silica sol and performing supercritical drying to obtain modified silica; S200, mixing the modified polypropylene, the modified silicon dioxide, the reinforcing material and the reaction aid, and performing melt mixing, sheet casting and mechanical stretching to obtain a polypropylene base film; S300, performing vacuum evaporation treatment on the polypropylene base film, including sequentially performing base film pretreatment, first evaporation treatment, first oxidation treatment, second evaporation treatment and second oxidation treatment.

2. The preparation process according to claim 1, characterized in that: The specific process of preparing the polymer sol is as follows: Add N-methyl-2-pyrrolidone, p-xylene and dimethylacetamide into a vacuum reactor, set the vacuum degree to ≤20Pa, and stir evenly at 30°C; add 1,2,4-trimethylbenzene anhydride and 4,4'-methylenebis(phenyl isocyanate), raise the temperature to 50°C and keep the temperature constant for 60 minutes; add diphenylmethane diisocyanate and phenol, stir evenly and keep the temperature constant for 60 minutes to obtain the polymer sol.

3. The preparation process according to claim 1, characterized in that: The specific process of preparing the silica sol is as follows: Ethyl orthosilicate, ethanol and deionized water were mixed evenly, hydrochloric acid solution was added dropwise to adjust the pH value to 5, and the mixture was stirred at a constant temperature of 40° C. for 10 minutes; sodium hydroxide aqueous solution was added dropwise to a pH value of 10, and the mixture was stirred at a constant temperature of 40° C. for 60 minutes, and allowed to stand for 120 minutes to obtain the silica sol.

4. The preparation process according to claim 1, characterized in that: The supercritical drying is carried out under the following conditions: With carbon dioxide as the medium, the temperature is 31°C to 33°C, and the pressure is 7.3MPa to 7.5MPa.

5. The preparation process according to claim 1, characterized in that: In the preparation of the polypropylene-based film: the weight average molecular weight Mw of the modified polypropylene is 400,000, and the melt flow rate is 10 g / 10 min; The reinforcing material comprises polyetherimide chopped fibers and nano zirconium boride in a weight ratio of 1:5; The reaction aid comprises γ-aminopropyltriethoxysilane and polyvinyl alcohol in a weight ratio of 1:

8.

6. The preparation process according to claim 1, characterized in that: The basement membrane pretreatment comprises: The method comprises the following steps: performing corona discharge treatment twice, wherein the primary corona discharge treatment energy is 20-25 J / cm2 and the secondary corona discharge treatment energy is 50-52 J / cm2; applying 2-3‰ ammonium chloride solution between the two corona discharge treatments and drying at 85-90°C.

7. The preparation process according to claim 1, characterized in that: The process parameters of the first evaporation are: the cooling spindle temperature is 0-1°C; the zinc crucible heating temperature is 780-790°C.

8. The preparation process according to claim 1, characterized in that: The process parameters of the first oxidation treatment are: A mixed gas of ozone and nitrogen with a volume fraction of 5-6‰ is introduced into a constant temperature oven at 120-125°C.

9. The preparation process according to claim 1, characterized in that: The process parameters of the second evaporation are: The cooling spindle temperature is -3~-1℃; The heating temperature of the aluminum crucible is 1590~1600℃; Control the thickness of the aluminum coating to half of the galvanized coating.

10. The preparation process according to claim 1, characterized in that: The second oxidation treatment uses hydrogen peroxide with a mass fraction of 65-70% and performs surface oxidation treatment at 50-55°C.